2020
DOI: 10.1002/btm2.10171
|View full text |Cite
|
Sign up to set email alerts
|

Personalized‐induced neural stem cell therapy: Generation, transplant, and safety in a large animal model

Abstract: In this study, we take an important step toward clinical translation by generating the first canine-induced neural stem cells (iNSCs). We explore key aspects of scale-up, persistence, and safety of personalized iNSC therapy in autologous canine surgery models. iNSCs are a promising new approach to treat aggressive cancers of the brain, including the deadly glioblastoma. Created by direct transdifferentiation of fibroblasts, iNSCs are known to migrate through the brain, track down invasive cancer foci, and deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Effector molecules that have been used to regulate tumor growth include tumor necrosis factor apoptosis-inducing ligand (TRAIL), interferons ( / ), interleukins (ILs), and single-chain antibodies [ 59 , 60 ]. The antitumor effects of SCs expressing TRAIL have been extensively studied in GBM [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. TRAIL is a pro-apoptotic ligand that binds to death receptor (DR) 4 and 5 on cancer cells.…”
Section: A Glance At the Futurementioning
confidence: 99%
See 3 more Smart Citations
“…Effector molecules that have been used to regulate tumor growth include tumor necrosis factor apoptosis-inducing ligand (TRAIL), interferons ( / ), interleukins (ILs), and single-chain antibodies [ 59 , 60 ]. The antitumor effects of SCs expressing TRAIL have been extensively studied in GBM [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. TRAIL is a pro-apoptotic ligand that binds to death receptor (DR) 4 and 5 on cancer cells.…”
Section: A Glance At the Futurementioning
confidence: 99%
“…Though TRAIL stem cell-based therapies have shown to be efficacious in small-animal models, more clinically relevant models are warranted to determine their clinical utility. In an attempt to explore personalized, induced neural stem cell therapy for GBM, Bomba et al generated, transplanted and investigated the safety of iNSCs in a canine model [ 68 ]. Interestingly, pathology findings concluded no signs of abnormal pathology post-mortem and in vitro studies revealed that canine iNSC-sTR maintained their tumoritropic migratory properties and tumor killing capability.…”
Section: A Glance At the Futurementioning
confidence: 99%
See 2 more Smart Citations
“…Induced neural stem cells (iNSCs), cells that undergo transdifferentiation from the patients’ skin, are used as drug carriers with an innate tropism to neural cells including GB [ 127 ]. These cell derivatives can be genetically engineered to express cytotoxic proteins, which aid in cancer destruction as the cells will naturally migrate towards the cancer-invading area [ 127 ]. The iNSCs could carry therapeutic agents such as TNF α, and thymidine kinase [ 127 ].…”
Section: Cell Therapy For Glioblastomamentioning
confidence: 99%